ANALISIS VALUASI PERUSAHAAN STARTUP DIGITAL: STUDI KASUS PADA KOSTPEDIA.ID - Ni Komang Sri Artani; Ni Made Estiyanti; Eddy Muntina Dharma (Badung: LPPM Universitas Triatma Mulya, 2019)
The purpose of this research is determine the value of startup valuation from qualitative and quantitative factors on startup kostpedia.id. Kostpedia.id is a platform to help migrants in Indonesia to find and order residential dwellings. Kostpedia needs funds to support all of its operational and development activities, such as introducing Kostpedia.id to residents of rent and needs its own office. To get funding from investors requires startup valuation using the scorecard valuation method. Scorecard valuation method, which is a method for comparing similar companies at the same developmental stage with non-financial indicators.